2020
DOI: 10.11591/eei.v9i2.2101
|View full text |Cite
|
Sign up to set email alerts
|

A prosthetic limb managed by sensors-based electronic system: Experimental results on amputees

Abstract: Taking the advantages offered by smart high-performance electronic devices, transradial prosthesis for upper-limb amputees was developed and tested. It is equipped with sensing devices and actuators allowing hand movements; myoelectric signals are detected by Myo armband with 8 ElectroMyoGraphic (EMG) electrodes, a 9-axis Inertial Measurement Unit (IMU) and Bluetooth Low Energy (BLE) module. All data are received through HM-11 BLE transceiver by Arduino board which processes them and drives actuators. Raspberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…The initial search yielded 108 articles. Once the duplicates were removed and eligibility criteria were applied, 10 articles with a total of 180 participants were included in the review [ 4 , 7 , 9 , 10 , 11 , 18 , 19 , 20 , 21 , 22 ]. The characteristics of included studies are shown in Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 108 articles. Once the duplicates were removed and eligibility criteria were applied, 10 articles with a total of 180 participants were included in the review [ 4 , 7 , 9 , 10 , 11 , 18 , 19 , 20 , 21 , 22 ]. The characteristics of included studies are shown in Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Burboa et al, (17) en su estudio, llevaron a cabo una relación entre los efectos del entrenamiento con respecto a los cambios en la angulación articular de miembros inferiores, encontrando que sí existe relación entre la fatiga generada en una sesión y los cambios en la angulación articular, siendo evidente la fiabilidad de las IMU en estas actividades. De igual manera, se emplearon como herramientas para la realización de evaluación de movimientos en diferentes entornos (13) , haciendo uso de ellos en gran medida, en estudios relacionados con los parámetros de la marcha, en la medición de variables como velocidad, posicionamiento de los miembros inferiores (10) , parámetros anormales de la marcha (11) y estimación de la rotación del movimiento de los usuarios para ser recreados y analizados con mayor profundidad en softwares de análisis de movimiento (51) .…”
Section: Discussionunclassified
“…Today technology is increasingly in close contact with humanity, an inseparable bond that promises, used with intellect and parsimony, to improve our lives in every aspect [ 1 , 2 , 3 ]. Thanks to the Internet of Things (IoT), these technologies allow us to be connected and keep under control every aspect of our life, from the home to the car, to health monitoring [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%